Synthesis of Multi-walled Carbon Nanotubes/ZnO Nanocomposites using Absorbent Cotton - Qu, Jiao; Luo, Chunqiu; Cong, Qiao (Nano-Micro Letters, 2011)
This letter focuses on the synthesis of multi-walled carbon nanotubes (MWNTs) and MWNTs/ZnO nanocomposites using absorbent cotton. The MWNTs have been synthesized by a rapid heating of absorbent cotton at different temperature (400°C, 550°C, 600°C). The MWNTs/ZnO nanocomposites have been synthesized by heating mixtures of Zn(OH)2/H2O/absorbent cotton at different temperature (at about 550°C and 600°C). The X-ray diffraction (XRD) pattern and energy dispersive spectrum (EDS) clearly show that the pure MWNTs and ZnO nanocomposites (with a mean size of 35.9 nm) were synthesized. The scanning electron microscopy (SEM) images demonstrate that the structure of synthesized MWNTs was middle-hollow, with inner and outer diameter of around 10 and 80 nm. The ZnO nanocomposites that had grown on the walls of MWNTs were nonuniform and agglomerated, with an outer diameter of around 110 nm. The selected area diffraction (SAD) patterns and Raman spectrum indicate that the MWNTs were well-crystallised, and there are a few defects in the walls. Infrared absorption spectroscopy (IR) spectra suggest that the surface of MWNTs has been covered by ZnO.